Measuring Vote-Selling: Field Evidence from the Philippines - Hicken, Allen; Leider, Stephen; Ravanilla, Nico; Yang, Dean (American Economic Review, 2015)
Using data from an anti-vote-buying field experiment we conducted in the Philippines, we report and validate a proxy measure for vote-selling. We demonstrate that our proxy measure, vote-switching, changes as expected with voter preferences and monetary offers from candidates. Voters are less likely to vote for someone different than their initial preference the larger the favorability rating difference between the preferred and alternative candidates. Similarly, vote-switching increases the more money the alternative candidate offers compared to the preferred candidates. We also describe the effects of the promise-based interventions on vote-switching, reported in full in a companion paper.